IL-17A+GM-CSF+ Neutrophils Are the Major Infiltrating Cells in Interstitial Lung Disease in an Autoimmune Arthritis Model - Kwon, Oh Chan; Lee, Eun-Ju; Chang, Eun-Ju; Youn, Jeehee; Ghang, Byeongzu; Hong, Seokchan; Lee, Chang-Keun; Yoo, Bin; Kim, Yong-Gil (Frontiers in Immunology, 2018)
Objective. To gain a better understanding of the pathogenesis of autoimmune arthritis-associated interstitial lung disease (ILD), we sought to identify the characteristics of lung-infiltrating cells in SKG mice with ILD. Methods. We injected curdlan in SKG mice at 8 weeks of age, and identified the presence of ILD by PET-MRI at 20 weeks post-injection and histological analysis at 22 weeks post-injection. Lung-infiltrating cells were examined by flow cytometry. Analysis of serum cytokines by the Luminex multiplex cytokine assay was performed at 14 and 22 weeks post-injection, and cytokine profiles before and after the development of ILD were compared. Opal multiplexed immunofluorescent staining of lung tissue was also performed. Results. At 20 weeks post-injection, curdlan-treated SKG mice developed not only arthritis but also lung inflammation combined with fibrosis, which was identified by PET-MRI and histological analysis. The majority of inflammatory cells that accumulated in the lungs of curdlan-treated SKG mice were CD11b+Gr1+ neutrophils, which co-express IL-17A and GM-CSF, rather than TNF-α. Compared with 14 weeks post-injection, serum levels of GM-CSF, MCP1, IL-17A, IL-23, TSLP, and soluble IL-7Rα had increased at 22 weeks post-injection, whereas those of IFN-, IL-22, IL-6, and TNF-α remained unchanged. Furthermore, IL-23, CXCL5, IL-17A, and GM-CSF, but not TNF-α, were observed in immunofluorescent-stained lung tissue. Conclusion. We found that IL-17A+GM-CSF+ neutrophils represented the major inflammatory cells in the lungs of curdlan-treated SKG mice. In addition, GM-CSF and IL-17A appear to play a more important role than TNF-α in ILD development.